Preventing online shopping for completed assessments: Protecting students by blocking access to contract cheating websites on institutional networks - Seeland, Josh; Stoesz, Brenda M; Vogt, Lisa (Canadian Perspectives on Academic Integrity, 2020)
Contract cheating or “the outsourcing of student work to third parties” (Lancaster & Clarke, 2016, p. 639) is a type of academic misconduct that is growing and changing due to advancements in technology and the emergence of a lucrative, multi-million dollar per year industry that targets students relentlessly (Lancaster & Clarke, 2016). In an effort to protect students from engaging in contract cheating, three postsecondary institutions in Manitoba (i.e., Assiniboine Community College, Red River College, and the University of Manitoba) launched initiatives to block access to websites that offer contract cheating services from their networks. This initiative facilitated a preliminary examination of student activity on institutional networks. In any given month, a relatively large number of students (i.e., up to 3,519 unique users) were attempting to access websites identified as providing contract cheating services. We recognize that a single initiative will not eliminate academic misconduct, however, by combining various educational, protective, and preventative strategies, the likelihood that students will make ethical decisions regarding their academic work can be increased.